IMPLEMENTASI SISTEM INFORMAS MANAJEMEN DAERAH (SIMDA) TERHADAP PELAPORAN KEUANGAN DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KUTAI BARAT - Mamang, Arniati A. DG. (EKONOMIA, 2019)
This study is to discuss the Implementationof Regional Management Information Systems (SIMDA) in the Department of Manpower and Transmigration in West Kutai Regency as one ofthe assistants incarrying out financial management and accountability to the government. The analysis used is the suitability of financial management and financial reporting based on applicable government regulations. The method used is a qualitative research method.The implementation of the Regional Management Information System (SIMDA) as a helper software in financial management has been implemented optimally but it is necessary to supervise the use of the system by the leadership so that financial management and financial reporting have more high accountability and avoid deviant or inappropriate things with the prevailing laws and regulations in the implementation of financial management main duties and fctions in accordance with the Government Regulation of the Republic of Indonesia Number 58 of 2005 concerning Regional Financial Management.The implementation of the Regional Management Information System (SIMDA) as a supporting software in the accountability of the preparation of financial statements has been implemented maximally in accordance with the Government Regulation of the Republic of Indonesia Number 71 of 2010 concerning Government Accounting Standards.